THEMATIC CONTENT OF THE RADIO AS A CONDITION FOR SUCCESSFUL INTERACTION IN THE MEDIA DISCOURSE (ON THE EXAMPLE OF THE REGIONAL RADIO STATION «KAZAK FM») (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-196-205In our time, there has been a tendency to search for complex, serious topics for the air. People are interested in all spheres of life, and all topics relevant to society need their unconditional discussion. The radio host constantly needs to add questions that can attract the listener to the receiver, surprise him and push him into discussion. This is the job of an experienced DJ. The aim of the work is to determine the main components of successful radio communication of the regional radio discourse. Particular attention is paid to the thematic content of the radio broadcast.The main methods in the work are analysis and synthesis. Based on the analysis of the texts of the Kazak FM radio station, we draw conclusions about the need for a clear choice and justification of the creative task, professional competence in developing the theme of the air and indispensable literary skill as a whole complex that makes up the success of the air of any modern radio station.The novelty of our work lies in the fact that the media texts of a regional radio station, which have not yet been introduced into scientific circulation, served as the material for analysis. The task of the unique and original channel is to create a variety of service and socially significant elements that affect the most interesting aspects of the life of the region, in particular culture, history, medicine, tourism, economic development and sports. The system of interaction “addressee-addresser” as elements of successful communication includes both thematic content of the radio air, and the role of the presenter, his journalistic activity and professional skills. Only the combination of these factors leads to success.Keywords: thematic content, journalistic skills, communication, radio, image of the presenter, addressee, addressee, «Kazak FM»